Schools as mediators of immigrant children’s cognitive performance: Young international students - Figueiredo, Sandra (Journal of International Students, 2026)
This study investigates whether such disparities account for notable differences in students’ academic performance. Using a multiple-case study design, we examined the impact of school-level variables and available educational resources—particularly language proficiency testing—on the performance of 36 immigrant learners across three custom-developed tasks: verbal reasoning, vocabulary, and writing. Data were analyzed through structural equation modeling (SEM) and confirmatory factor analysis (CFA) in AMOS to assess whether students’ outcomes were significantly influenced by school characteristics and the presence of targeted resources. The findings indicate that institutional practices and tailored resources significantly affect students’ academic outcomes. Students attending schools without structured support measures and differentiated instruction for low-proficiency learners exhibited lower performance across all tasks. While nationality and mother tongue were relevant predictors when the school factor was controlled, socioeconomic status (SES) demonstrated predictive power only within the confirmatory analysis.